Diagnostic Comparison of Elevated Fecal Leukocytes and sTREM-1 in Children with Acute Diarrhea Caused by Bacterial Infection - Yudiyanto, Ade Rachmat; Firmansyah, Agus; Karyanti, Mulya Rahma (Journal La Medihealtico, 2025)
Diarrhea is a health problem that most often occurs in children. Various etiologies of diarrhea can cause prolonged diarrhea and become malnourished (malnutrition). The etiology of diarrhea can be caused by a bacterial infection and requires antibiotics, so that detection is needed as early as possible. Examination of soluble triggering expressed receptors on myeloid cells-1 (sTREM-1) can predict bacterial infection in children with acute diarrhea. The study aims to know how much the diagnostic value of fecal leukocytes test compared to sTREM-1. A cross-sectional study of children aged 6-60 months with acute diarrhea without complications and other diseases. In the subjects, clinical manifestation was performed (fever, vomiting, abdominal pain), fecal leukocyte test and sTREM-1 test as a standard reference. Children, aged 6-60 months with acute diarrhea due to bacterial infections with sTREM-1 > 470 pg/mL as many as 2 of 64 subjects and fecal leukocytes > 10/HPF as many as 14 of 64 subjects, most male, normal nutritional status and had clinical manifestation of fever, vomiting and without abdominal pain. Increased fecal leukocytes > 10 / HPF has a sensitivity of 50%, specificity 79.1%, positive predictive value 7.1%, negative predictive value 98%, accuracy 78%, positive likelihood ratio 2.18 and negative likelihood ratio 0.63. Fecal leukocyte test > 10/HPF as a diagnostic confirmation is not good in diagnosing acute diarrhea due to bacterial infection.